Competency level of teachers in the Agroindustry chair in a distance university (UNED Research Journal, 2018)
In distance education, tutors need skills such as accessibility and motivation; virtual socialization; information exchange, and knowledge construction and development. We determined which of these skills were being applied in two courses of a Costa Rican distance university. We used a validated survey applied to all the teachers of the Agroindustry chair (three) and validated checklist applied to two courses. We only found satisfactory results in one course. Tutors have a tendency towards planning; stimulating collaborative work among students; criteria unification and use of pedagogical strategies. On the other hand, we realized how some tutors do not identify the way students learn; knowledge networks are not created as well as mutual knowledge outside the classroom. Finally, some tutors do not have formal training in virtual classrooms, although this did not have a negative impact in their performance as instructors. We recommend the implementation of formal training, collaborative workspaces and deeper acquaintance with the students.
Keywords: distance tutor; online tutor; distance education; educational competences